Validity and Reliability of Persian Version of the 12-Item Expectations Regarding Aging Survey. (March 2023) - Sharif Nia, Hamid; She, Long; Somasundram, Sotheeswari; Khoshnavay Fomani, Fatemeh; Kaveh, Omolhoda; Hosseini, Lida
Objective: The present study was designed to assess the construct validity and reliability of the Persian version of the 12-item Expectations Regarding Aging (ERA) survey among the older adult Iranian population.Methods: The Persian version of this scale was developed using translation and revision in the current study. The construct validity was assessed through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The reliability was assessed through internal consistency (Cronbach's alpha and McDonald's omega), composite reliability (CR), and maximal reliability (MaXR). The data compiled online was based on a sample of 400 older adults aged 65 years and older.Results: The Persian version includes 12 items loading onto three factors with 12 items explaining 46.633% of the total variance with excellent internal consistency and reliability.Conclusion: The Persian version of ERA is reliable and valid that can be used to assess the ERA concept among older adults.